Common cortical architectures for phonological working memory identified in individual brains - Scott, Terri L.; Perrachione, Tyler K. (NeuroImage (Orlando, Fla.), 2019)
Phonological working memory is the capacity to briefly maintain and recall representations of sounds important for speech and language and is believed to be critical for language and reading acquisition. Whether phonological working memory is supported by fronto-parietal brain regions associated with short-term memory storage or perisylvian brain structures implicated in speech perception and production is unclear, perhaps due to variability in stimuli, task demands, and individuals. We used fMRI to assess neurophysiological responses while individuals performed two tasks with closely matched stimuli but divergent task demands—nonword repetition and nonword discrimination—at two levels of phonological working memory load. Using analyses designed to address intersubject variability, we found significant neural responses to the critical contrast of high vs. low phonological working memory load in both tasks in a set of regions closely resembling those involved in speech perception and production. Moreover, within those regions, the voxel-wise patterns of load-related activation were highly correlated between the two tasks. These results suggest that brain regions in the temporal and frontal lobes encapsulate the core neurocomputational components of phonological working memory; an architecture that becomes increasingly evident as neural responses are examined in successively finer-grained detail in individual participants.